Optimization of rainfall gauging system for rainfall-runoff for lipis river - Nur Wahida, Mohd Zawawi (2016)
This study is focused on optimization of rainfall gauging system for rainfall runoff at Lipis River, Pahang. The rainfall-runoff model is simulated using Hydrological Modelling System (HEC-HMS) version 3.5. HEC-HMS is software for use in analyzing, planning, and simulating the process of rainfall and runoff. HEC-HMS 3.5 is used in this study to simulate discharge for Lipis River. This study uses rainfall data and stream flow data from January 2008 to December 2014. There are eleven rainfall stations and one stream flow station in Lipis River catchment area. The results of simulation can be generated in form of hydrograph, summary table, and time series table. Root Mean Square Error (RMSE) calculated to show the relationship of the simulated flow and the observed flow. If the RMSE value is lesser, it would indicate that the variables are positively linear related. During evaluation of model, the best value of RMSE value is 11.36 m³/s which is a low value. It shows that the simulated models were fit with the observed data and proves that the HEC HMS is suitable to predict and analyse rainfall-runoff relationship at Lipis River.